Perencanaan Sistem Instalasi Plambing Air Bersih dengan Penerapan Alat Plambing Hemat Air Di Rumah Sakit Universitas Sam Ratulangi - Adeyra Khairunisa Rahayu; Yulianti Pratama; Anindito Nurprabowo (Jurnal Serambi Engineering, 2020)
The hospital is a health service building, a place of transmission of disease and allows environmental pollution and health problems. One of the prevention of disease transmission and environmental pollution, it is necessary to do repairs and improvements by using a plumbing system to have good sanitation and environmental friendly. In this case, needed to know how much water can save by method comparing between plumbing tools conventional and non-conventional standar. UNSRAT’s hospital has a population of 2,962 people who needed clean water distribution of 372,48 m3/ day. Compared by using conventional plumbing tools is 66,72 m3/hari, meanwhile non-conventional plumbing tools is 39,60 m3/hari, it shown that using non-conventional plumbing  tools standard is more saving than conventional standard, where percentage non-conventional water saving is 40,64%. Also expected that the resulting domestic wastewater will be reduced by 31,68 m3/ day. This is more important than water savings in the amount of Rp. 3.564.000 and domestic wastewater treatment costs Rp. 9.500.000.